Motor cortex and spinal cord neuromodulation promote corticospinal tract axonal outgrowth and motor recovery after cervical contusion spinal cord injury - Zareen, N.; Shinozaki, M.; Ryan, D.; Alexander, H.; Amer, A.; Truong, D.Q.; Khadka, N.; Sarkar, A.; Naeem, S.; Bikson, M.; Martin, J.H. (Experimental neurology, 2017)
Cervical injuries are the most common form of SCI. In this study, we used a neuromodulatory approach to promote skilled movement recovery and repair of the corticospinal tract (CST) after a moderately severe C4 midline contusion in adult rats. We used bilateral epidural intermittent theta burst (iTBS) electrical stimulation of motor cortex to promote CST axonal sprouting and cathodal trans-spinal direct current stimulation (tsDCS) to enhance spinal cord activation to motor cortex stimulation after injury. We used Finite Element Method (FEM) modeling to direct tsDCS to the cervical enlargement. Combined iTBS-tsDCS was delivered for 30min daily for 10days. We compared the effect of stimulation on performance in the horizontal ladder and the Irvine Beattie and Bresnahan forepaw manipulation tasks and CST axonal sprouting in injury-only and injury+stimulation animals. The contusion eliminated the dorsal CST in all animals. tsDCS significantly enhanced motor cortex evoked responses after C4 injury. Using this combined spinal-M1 neuromodulatory approach, we found significant recovery of skilled locomotion and forepaw manipulation skills compared with injury-only controls. The spared CST axons caudal to the lesion in both animal groups derived mostly from lateral CST axons that populated the contralateral intermediate zone. Stimulation enhanced injury-dependent CST axonal outgrowth below and above the level of the injury. This dual neuromodulatory approach produced partial recovery of skilled motor behaviors that normally require integration of posture, upper limb sensory information, and intent for performance. We propose that the motor systems use these new CST projections to control movements better after injury. We used a neuromodulatory strategy to promote motor function after a C4 contusion injury in rats. This strategy comprises bilateral motor cortex epidural intermittent theta burst (iTBS) electrical stimulation, to promote CST axonal sprouting, and cathodal trans-spinal direct current stimulation (tsDCS), to enhance the spinal cord activation of iTBS after injury. This dual neuromodulatory strategy promoted skilled forelimb movements and CST repair. At 6weeks, injury+stimulation animals showed significant improvement in forelimb manipulation scores at the end of the study (dotted line shows raw data; solid line, smoothed data; 9 corresponds to ideal performance; Kolmogorov-Smirnoff test; p<0.05). At 6weeks skilled locomotion was significantly improved only in the stimulated group. Combined stimulation resulted in an increase in the gray matter CST axon length caudal to the injury (heat map insets). Our data show that a combined motor cortex and cervical spinal cord neuromodulatory approach improves skilled forelimb movements and CST sprouting after cervical SCI. [Display omitted] •Cathodal tsDCS was directed to the injured cervical enlargement using FEM modeling.•tsDCS enhanced motor cortex evoked responses after C4 injury in rats.•Combined iTBS and tsDCS improved horizontal ladder walking and manipulation skills.•Neuromodulation enhanced CST outgrowth above and below the injury.•Neuromodulation has translational potential for neural repair and motor recovery cervical SCI.